Analisis Penerapan E-Faktur Pajak Dalam Upaya Meningkatkan Kepatuhan Pengusaha Kena Pajak Untuk Pelaporan SPT Masa PPN Tahun 2021-2022 Di KPP Pratama Manado - Makalare, Zevania Meysha; Sondakh, Jullie J.; Pangerapan, Sonny (Universitas Sam Ratulangi, 2023)
The rapid development of technology has encouraged tax authorities around the world to use it for tax administration, one of which is managing electronic tax invoices through the e-Invoice application. This research aims to analyze how tax e-invoicing is implemented in an effort to increase the compliance of Taxable Entrepreneurs for reporting VAT SPT for the 2021-2022 period. The analytical method used in this research is a qualitative descriptive method. The results obtained from this research show that the level of compliance of taxable entrepreneurs using e-invoices in 2021 is 90.45% and in 2022 it is 86.97%. This shows that the implementation of e-invoicing is classified as less compliant because the percentage from 2021 to 20222 has decreased.